Generalized Envelope-Based Modeling of Single-Phase Grid-Connected Power Converters - Azcondo, Francisco J.; Pigazo, Alberto; Brañas, Christian; Lamo-Anuarbe, Paula; Díaz, F. Javier; Casanueva, Rosario (IEEE Transactions on Industrial Electronics, 2024)
In-depth models of single-phase grid-tied power converters facilitate the examination of low-frequency (LF) interactions among loads, distributed energy resources (DERs), and synchronous generators by operators and designers. These interactions are becoming increasingly significant with the growing integration of power electronics into electrical grids. This article extends the envelope modeling (EM) technique to develop LF linear time-invariant (LTI) circuit models for single-phase grid-tied power converters. The models utilize an independent phase signal that aligns with the most appropriate reference frame. This methodology preserves the LF dynamics inherent to the power converter and control system. The practicality of this method is evidenced by constructing a model for a bridgeless totem-pole power factor corrector (PFC), which includes a zero-crossing detector (ZCD) and operates without closed-loop regulation. The outcomes from this model are juxtaposed with those from a switched model and other well-stablished modeling techniques for comparison. Furthermore, a commercially available circuit design featuring current and voltage control loops is simulated, and the results are corroborated with experimental data. These experiments are conducted under disturbances influencing the converter’s performance within its linear operational range.
Keywords: integrated circuit modeling; switches; frequency conversion; voltage; synchronization; voltage control; switching circuits; envelope modeling (EM); grid-connected converter; power factor correction (PFC)